Effect of a Thin Fluid Layer on Surface Wave Speed Measurements: A Lung Phantom Study. (12th September 2018) - Zhou, Jinling; Zhang, Xiaoming
Abstract : Lung ultrasound (US) surface wave elastography (SWE) is a novel technique that measures superficial lung tissue elastic properties. A thin pleural fluid layer covers a lung, but its effect on lung measurements in SWE is unknown. We modeled a lung and pleural fluid with sponges and a thin layer of US transmission gel. Sponge surface wave speeds measured from SWE were compared for sponges without and with the thin US gel layer at 3 wave excitation frequencies. The comparison showed that the sponge surface wave speed measurements were not affected by the thin gel layer.